STUDENTS’ METACOGNITIVE STRATEGY IN WRITING DESCRIPTIVE TEXT AT SENIOR HIGH SCHOOL - Vebiona Frendi; Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This study aims to analyze Students’ Metacognitive Strategy in Writing Descriptive Text at Senior High School. The objectives of the study were to investigate the aspects of metacognitive strategy that students of tenth grade Mas Plus Al-Ulum use in writing descriptive text. This study was conducted by using descriptive qualitative method. The data analyzed by O’malley and Chamot. This study found that were 3 aspects of metacognitive strategy namely, Planning ; Monitoring; and Evaluation. The findings showed that the planning become more dominant aspects that use by students. It can be seen from the observation and the questionaire that give by researcher. Total responses of planning classification were 23.2%. There were (5.8%) Advance Organizers, (3.6%) Directed Attention, (4.4%) Functional Planning, (2.7%) Selective attention, and (6.7%) Self Management. Therefore, total response of monitoring were 21.1%, and evaluation 11.1%.Keywords: Metacognitive Strategy, Writing Skill, Descriptive Text, Qualitative Research Methodology